2023
DOI: 10.3847/1538-4357/ad0df8
|View full text |Cite
|
Sign up to set email alerts
|

Velocity-space Signatures of Resonant Energy Transfer between Whistler Waves and Electrons in the Earth’s Magnetosheath

Wence Jiang,
Daniel Verscharen,
Seong-Yeop Jeong
et al.

Abstract: Wave–particle interactions play a crucial role in transferring energy between electromagnetic fields and charged particles in space and astrophysical plasmas. Despite the prevalence of different electromagnetic waves in space, there is still a lack of understanding of fundamental aspects of wave–particle interactions, particularly in terms of energy flow and velocity-space characteristics. In this study, we combine a novel quasilinear model with observations from the Magnetospheric Multiscale mission to reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…However, direct evidence is needed to support the contribution of PUIs to the formation of plateau-like spectra. Numerous studies suggest that the magnetic field spectrum comprises diverse wave modes and structures, including Alfvén waves, fast-mode/slow-mode magnetosonic waves, and coherent structures such as filamentary Alfvén vortices, current sheets, and magnetic holes (Sahraoui et al 2006;Alexandrova 2008;Vörös et al 2008;Lion et al 2016;Jiang et al 2022Jiang et al , 2024. The spectral shape and location of the break point suggest the presence of narrowband waves, incoherent and unpolarized fluctuations, and coherent structures with significant amplitudes (Lion et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, direct evidence is needed to support the contribution of PUIs to the formation of plateau-like spectra. Numerous studies suggest that the magnetic field spectrum comprises diverse wave modes and structures, including Alfvén waves, fast-mode/slow-mode magnetosonic waves, and coherent structures such as filamentary Alfvén vortices, current sheets, and magnetic holes (Sahraoui et al 2006;Alexandrova 2008;Vörös et al 2008;Lion et al 2016;Jiang et al 2022Jiang et al , 2024. The spectral shape and location of the break point suggest the presence of narrowband waves, incoherent and unpolarized fluctuations, and coherent structures with significant amplitudes (Lion et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Shi et al (2020) showed that whistlers at the bow shock effectively scatter electrons and modify the electron distribution. In a recent numerical study, Jiang et al (2023) modeled a MSH electron distribution during the excitation of whistler waves. They observed that energy transfer mainly occurred through the first-order cyclotron resonance and that the interaction caused a reduction of the electron temperature anisotropy.…”
Section: Introductionmentioning
confidence: 99%